Pre-existent NRTI and NNRTI resistance impacts on maintenance of virological suppression in HIV-1-infected patients who switch to a tenofovir/emtricitabine/rilpivirine single-tablet regimen. (19th December 2016) - Armenia, D.; Di Carlo, D.; Calcagno, A.; Vendemiati, G.; Forbici, F.; Bertoli, A.; Berno, G.; Carta, S.; Continenza, F.; Fedele, V.; Bellagamba, R.; Cicalini, S.; et al.
Abstract : Objectives: To evaluate the maintenance of virological suppression (VS) in antiretroviral-treated HIV-1-suppressed patients switching to a tenofovir/emtricitabine/rilpivirine (TDF/FTC/RPV) single-tablet regimen, by considering pre-existent resistance (pRes). Methods: pRes was evaluated according to resistance on all previous plasma genotypic resistance tests. Probability and predictors of virological rebound (VR) were evaluated. Results: Three hundred and nine patients were analysed; 5.8% of them showed resistance to both NRTIs and NNRTIs, while 12.6% showed resistance to only one of these drug classes. By 72 weeks, the probability of VR was 11.3%. A higher probability of VR was found in the following groups: (i) patients with NRTI + NNRTI pRes compared with those harbouring NRTI or NNRTI pRes and with those without reverse transcriptase inhibitor pRes (39.2% versus 11.5% versus 9.4%, P < 0.0001); (ii) patients with a virus with full/intermediate resistance to both tenofovir/emtricitabine and rilpivirine compared with those having a virus with full/intermediate resistance to tenofovir/emtricitabine or rilpivirine and those having a virus fully susceptible to TDF/FTC/RPV (36.4% versus 17.8% versus 9.7%, P < 0.001); and (iii) patients with pre-therapy viraemia >500 000 copies/mL compared with those with lower viraemia levels (>500 000: 16.0%; 100 000–500 000: 9.3%; <100 000 copies/mL: 4.8%, P = 0.009). pRes and pre-therapy viraemia >500 000 copies/mL were independent predictors of VR by multivariable Cox regression. Conclusions: TDF/FTC/RPV as a treatment simplification strategy shows a very high rate of VS maintenance. The presence of pRes to both NRTIs and NNRTIs and a pre-therapy viraemia >500 000 copies/mL are associated with an increased risk of VR, highlighting the need for an accurate selection of patients before simplification.